The Pharmacokinetics of Beraprost Sodium Following Single Oral Administration to Subjects With Impaired Kidney Function. (15th November 2016) - Shimamura, Masahiro; Miyakawa, Jun; Doi, Masaaki; Okada, Kiyonobu; Kurumatani, Hajimu; Mori, Yoshitaka; Oshida, Keiyu; Nakajo, Ikumi; Oikawa, Keishi; Ushigome, Fumihiko; Miyashita, Aiji; Isono, Masanao; et al.
Abstract: The purpose of the present study was to evaluate the pharmacokinetics of beraprost sodium (BPS) and its active enantiomer, BPS‐314 d, in Japanese subjects with impaired kidney function. The plasma and urine concentrations of BPS and BPS‐314 d were measured following the single oral administration of 120 μg of BPS as the sustained‐release tablet, TRK‐100STP, under fasting conditions to 18 subjects with impaired kidney function (stage 2, 3, and 4 chronic kidney disease [CKD] as categorized by the estimated glomerular filtration rate) and to 6 age‐, body weight‐, and gender‐matched subjects with normal kidney function (stage 1 CKD). The Cmax values (mean ± SD) of BPS in stage 1, 2, 3, and 4 CKD, respectively, were 84.9 ± 22.9, 119.8 ± 36.4, 190.6 ± 137.3, and 240.2 ± 110.5 pg/mL; its AUC0‐48h were 978 ± 226, 1252 ± 427, 1862 ± 964, and 1766 ± 806 pg·h/mL, respectively, and its cumulative urinary excretion rates were 0.704 ± 0.351%, 0.638 ± 0.292%, 0.485 ± 0.294%, and 0.159 ± 0.136%. The Cmax values of BPS‐314 d were 22.4 ± 6.4, 30.8 ± 8.5, 46.7 ± 30.6, and 54.4 ± 25.2 pg/mL, its AUC0‐48h were 155 ± 56, 226 ± 67, 341 ± 176, and 329 ± 143 pg·h/mL, and its cumulative urinary excretion rates were 0.428 ± 0.242%, 0.349 ± 0.179%, 0.356 ± 0.270%, and 0.096 ± 0.099%, respectively. Adverse events were reported in 2 subjects with stage 2 CKD and 1 subject with stage 4 CKD. The Cmax and AUC0‐48h of BPS and BPS‐314 d were higher based on the severity of impaired kidney function. No relationship was observed between the incidence of adverse events and the severity, and tolerability was confirmed. We consider that dose adjustment is not necessary, but BPS is more carefully treated in patients with impaired kidney function.